Conflict aspects between French and Malay verbal systems - Omar, Hamid; Hassan @ Hussin, Omrah (Human Resource Management Academic Research Society, 2021)
Mother-tongue Interference in the acquisition of the target language is a commonplace for almost all foreign languages’ learners. In the case of Malaysian learners of French, it is somewhat different. The interference is occurring between two completely different linguistic systems, especially with regard to verbal systems. While the French verb informs us through its root and its infinitive form about the action to perform, and through its conjugated forms about the person, the number of persons performing the action, about the aspect and the tense of the action, the Malay verb, lacks all other information except the action to perform. These differences lead Malaysian learners of French to confuse between infinitive and conjugated verbs, between verb tenses and between conjugated verb endings, etc. In other words, it concerns the unconscious large interference between Malay and French languages that affects the structure and the meaning in French and, consequently, confuses the listener or the reader and causes communication to fail. The current study will focus on the conflict between French and Malay verbal systems. It does not agree with the approach of Representational Deficit Hypothesis and aims to promote a way based on the transformation of the explicit knowledge of French verbal grammar to implicit or almost implicit knowledge in order to avoid such conflict.